Elintarvikkeiden hintamarginaalit vuosina 1985-1996 - Laurinen, Heikki (Maatalouden taloudellinen tutkimuslaitos, 1996)
The study examines the development of marketing margins and consumer prices of foods products in Finland over 1985-1996. The purpose of these calculations is to indicate the distribution of the retail peices of the most important food products into the shares of raw material, processing and trade (=marketing margin) and taxes. The focus is on changes between situations before Finland s EU membership and after it. As an consequence of the membership, the producer prices decreased in Finland. The aim is to find out whether the decrease of producer prices went in full into the consumer prices. The price of food increased annually on ther average by 3,2 % in 1985-1991. As a consequence of increasing prices, the dissatisfaction against food prices increased: in 1990 only 7 % of consumers agreed that food prices in Finland are cheap of quite cheap. In 1991 producer prices started to fall.The phenomenon was a result of changes in agricultural policy. Moreover, the purchaging power was decreased by a strong economic depression. Also, the marketing margins of food products started to decrease. The most significant drop in marketing margins took place in 1993. In 1994, Finland started the adjustment into the EU membership. The decrease in marketing margins almost stopped. Due to the membership, the reduction of producer prices ranged between 30-60 %, on the average 40 %. The National Consumer Research Centre estimated that if the reduction of producer prices would go in full into the consumer prices the consumer prices of food products would decrease by 10 %. The results show that the reduction of producer price has gone in full into the consumer prices in meat, eggs, flour and bread. Compared with 1994, the marketing margins of meat decreased by 3-14 % in 1995 and consumer prices fell by 12-23 %. The decrease continued during the first quarter of 1996. The marketing margins of liquid milk have increased significantly, the marketing margins of emmenbtal cheese somewhat, whereas the marketing margins of edam cheese has decreased. On the average, the marketing margins of dairy products increased in 1995. Despite of that the profits of dairy processing industry decreased significantly. This is mainly due to the overproduction: collapse in export supsidies considerably decreased the profitability of export trade. Secondly, trade has increased it s margin due to the increased competition between dairies.
Keywords: Ma; hintamarginaalit; ravinnon hintakehitys; elintarvikkeiden tuonti; ruoankulutus; marketing margins; food consumption; food prices; food import